The influence of principals’ instructional leadership on teacher job satisfaction in Northwest China - Guo, Han; Alias, Bity Salwana; Wahab, Jamalullail Abdul (Journal of Education and Learning (EduLearn), 2026)
In education policy, principals’ teaching leadership is key to improving education quality. It shapes school culture and affects various aspects of school development, including teacher job satisfaction. However, there is a limitation of empirical research on how principal instructional leadership impacts teacher job satisfaction in Northwest China, a less developed area, highlighting a critical gap in understanding local educational dynamics. Therefore, this quantitative study aims to explain the impact of instructional leadership by principals on teacher job satisfaction in junior high schools across Ningxia, China. Underpinned by a correlational design, the study specifically focuses on the relationship between principal instructional leadership and teachers’ job satisfaction and the dimensions of instructional leadership that are most strongly associated with high levels of teacher job satisfaction. By analysing questionnaire responses from 372 randomly selected teachers, the research highlights that clear goal setting, effective curriculum coordination, and promoting professional development opportunities are important in improving teacher satisfaction. Interestingly, the study also shows that some commonly valued practices, such as high visibility and student progress monitoring, do not significantly influence teacher satisfaction. These findings highlight the importance of instructional leadership practices in improving teacher job satisfaction and suggest areas where school leaders can focus their efforts to enhance the overall educational environment.